Kindred spirits: friendship and resistance at the edges of modern Catholicism - Moore, Brenna (Class 200 new studies in religion, 2021)
"Kindred Spirits focuses on a network of Catholic historians, theologians, poets, and activists who pushed against both the far-right surge in interwar Europe as well as the secularizing tendencies of the leftist movements active in the early to mid-twentieth century. Brenna Moore focuses on how this group sought a middle way anchored in "spiritual friendship"-religiously meaningful friendship conceived of as uniquely capable of engaging the social and political challenges of the era. For this interconnected group, spiritual friendship was inseparable from their resistance to European xenophobia and nationalism in the 1930s, anti-racist activism in the US in the 1930s and 1940s, and solidarity with Muslims during the Algerian War in 1954-1962. Friendship was a key to both divine and human realms, a means of accessing the transcendent while also engaging with our social and political existence. The project primarily centers on France, but members of this group also hailed from Russia, Egypt, Syria, and New York. Some of the core figures are well-known-philosopher Jacques Maritain, influential Islamicist Louis Massignon-while others are lost to history. More than a simple idealized portrait of a remarkable group of Catholic intellectuals from the past, Kindred Spirits is a deep dive into both the beauty and the flaws of a vibrant social network worth recovering from historical obscurity"--